Empowerment of Milk Producers in Dairy Co-operative Societies Through Information Technology in Jaipur District of Rajasthan - Shringi , P. K.; Khan, I. M.; Verma, H. L. (Indian Journal of Extension Education, 2015)
Information Technology immense potential to for rural development and empowerment and it can help to deliver basic  services in more efficient and innovative ways.The present study was conducted in Jaipur district of Rajasthan. The Jaipur  dairy, is the largest computerised dairy cooperative society in Jaipur district of Rajasthan. From the Jaipur dairy two  chilling centers were selected, and from each selected chilling center three milk collection routes were selected randomly.  From each of the milk collection route, one computerized and one non-computerized dairy co-operative society (DCS)  was selected randomly. Therefore, a total of six computerized and six non-computerized dairy co-operative societies were  selected. From the selected DCSs, a total sample of 120 milk producers (60 non-computerized DCSs milk producers and  60 computerized DCSs milk producers) were selected for the present investigation. The data were collected by personal  interview method. The results of the study revealed that there was asignificant difference between the computerised and  non-computerised DCSs in all these indicators of access to information, facilitating improved decision making, formal  credit system and use fullness of the training programme. The highest difference between the computerised and non computerised DCSs was found in provision of immediate information about number of cattle (42.68%),computer based  new information serve to change people and bridge the gap between information rich and poor (54.36%), knowledge of  computer operation led to empowerment (57.08%), and training on computer handling (58.46%). The lowest difference  was found in provision of data to farmers on the seasonal variation in milk production (22.66%), participatory decision  about disbursing cattle insurance and loan (36.03%), smart card gives various information and detailed record about  individual milk producer as well as transparency and security about milk collection (35.71%) and proper storage of milk  (33.46%).The computerised DCSs was found significantly superior as compared to non-computerised DCSs.
Keywords: Dairy Co-operative Societies; IT; empowerment; milk producers